MUC13 contributes to rewiring of glucose metabolism in pancreatic cancer - Kumari, Sonam (Oncogenesis, 2018)
Pancreatic tumors are rewired for high-glucose metabolism and typically present with exceptionally poor prognosis. Recently, we have shown that MUC13, which is highly expressed in pancreatic tumors, promotes tumor progression via modulation of HER2 receptor tyrosine kinase activity. Herein, we investigate a novel, MUC13-mediated molecular mechanism responsible for higher glucose metabolism in pancreatic tumors. Our results demonstrate that MUC13 expression leads to the activation/nuclear translocation of NF-κB p65 and phosphorylation of IκB, which in turn upregulates the expression of important proteins (Glut-1, c-Myc, and Bcl-2) that are involved in glucose metabolism. MUC13 functionally interacts and stabilizes Glut-1 to instigate downstream events responsible for higher glucose uptake in pancreatic cancer cells. Altered MUC13 expression by overexpression and knockdown techniques effectively modulated glucose uptake, lactate secretion, and metastatic phenotypes in pancreatic cancer cells. NF-κB inhibitor, Sulfasalazine, abrogates the MUC13 and Glut-1 interaction, and attenuates events associated with MUC13-induced glucose metabolism. Pancreatic ductal adenocarcinoma (PDAC) patient tissue samples also show a positive correlation between the expression of these two proteins. These results delineate how MUC13 rewire aberrant glucose metabolism to enhance aggressiveness of pancreatic cancer and revealed a novel mechanism to develop newer therapeutic strategies for this exceptionally difficult cancer.